Awareness campaigns as survival tools in the fight against gender-based violence in peri-urban communities of Bulawayo in Zimbabwe - Glory Damba; Wilfred Lunga; Charles Musarurwa (Jàmbá, 2013)
Most of Zimbabwe’s urban settlements owe their existence to mining activities; hence most peri-urban communities around Bulawayo, Zimbabwe’s second largest city, are mining communities. However, research in these mining communities has shown that there is little focus on the strengthening of community dynamics that help members to cope with the challenges associated with Gender-Based Violence. Psychosocial support rarely arrives in time to effectively cover gaps left by traditional coping strategies. This paper presents and discusses experiences and insights accumulated from awareness campaigns meant to sensitise people about the nature and scope of gender-based violence. This article is a culmination of focus group discussions, informal interviews and participant observation as efforts were made towards capacity building for community members’ abilities to identify forms of risky behaviour associated with gender-based violence, and the appropriate actions members could take should they find themselves in such situations. In short, this article discusses the conceptualisation of domestic and gender violence as a risk, forms of gender-based violence, the rationale behind campaigns to reduce the internalisation of gender-based violence, and challenges faced in inculcating behaviour change efforts.